SAT-405 Trabecular Bone Score (TBS) in Primary Hyperparathyroidism (PHP): A Useful Tool? - Santos, Lívia Marcela (J Endocr Soc, 2020)
Background: PHP is a common disorder, and regardless of being an asymptomatic entity, often leads to bone loss and osteoporosis. TBS is a software-based assessment method of trabecular bone structure of the spine based on the analysis of pixels in dual energy x-ray absorptiometry (DXA) images. The aim of this study was to evaluate TBS measurements in combination with DXA values by searching for more accurate bone fragility risk assessment among PHP patients. Methods: From June/2017 to January/2019, all patients who met the criteria for PHP diagnosis prior to surgery were selected to take part in this study. Control group was composed by non-family related healthy volunteers. Bone mineral density (BMD) by DXA (DXA; Hologic QDR 4500) at the lumbar spine, total hip, femoral neck, distal third of the non-dominant radius and TBS values by InSight were determined in 64 PHP patients and 63 controls. Total and ionized calcium, PTH, 25-hydroxyvitamin D (25(OH)D), creatinine, alkaline phosphatase, P1NP and CTX were measured in all patients and control group. Results: Primary hyperparathyroidism patients presented significant lower BMD values in all evaluated sites compared to controls. TBS measurements were also statistically different among PHP patients and controls (mean TBS PHP=1233 vs TBS controls= 1280, p=0.044). Patients and controls didn’t differ in age, sex, menopausal state or BMI (body mass index). Osteoporosis diagnosis by DXA analysis was observed in 50% of PHP patients and in 26.6% of controls. Self-reported or image-diagnosed fracture occurred in 15 PHP (23.4%) patients and in 11 (17.5%) controls. Among these fractures, vertebral fracture account for 9 (14%) in PHP group and 4 (6.3%) in controls. ROC curve analysis showed that the TBS value < 1187 is associated to significant high risk of vertebral fracture (sensibility 87.5%, specificity 67.3%) among PHP patients. Conclusion: TBS, used as a complement to DXA measurements, is a useful tool to better assess fragility risk among PHP patients.